The arthropod, but not the vertebrate host or its environment, dictates bacterial community composition of fleas and ticks - Hawlena, Hadas (Nature Publishing Group, 2013)
Bacterial community composition in blood-sucking arthropods can shift dramatically across time and space. We used 16S rRNA gene amplification and pyrosequencing to investigate the relative impact of vertebrate host-related, arthropod-related and environmental factors on bacterial community composition in fleas and ticks collected from rodents in southern Indiana (USA). Bacterial community composition was largely affected by arthropod identity, but not by the rodent host or environmental conditions. Specifically, the arthropod group (fleas vs ticks) determined the community composition of bacteria, where bacterial communities of ticks were less diverse and more dependent on arthropod traits—especially tick species and life stage—than bacterial communities of fleas. Our data suggest that both arthropod life histories and the presence of arthropod-specific endosymbionts may mask the effects of the vertebrate host and its environment.